Análise quantitativa das relações entre usuários no twitter - Oliveira, Roberto Felicio de (2013)
Under the aspect of social beings, humans seek relentlessly interact with each other, in various occasions. This reality, expanded to the virtual world, which allows communication without borders through the Internet between people anywhere in the world. Thus, this dissertation aims to analyze quantitatively the relationships among Twitter users, through the use of Social Media monitoring tools combined with the techniques of Social Network Analysis, aiming to define the profile relationship of individuals within the scenario of which the same is inserted either in education or credit. Studies show that by applying the metrics degree of centrality, brokerage and centrality centrality proximity is possible to define the profile of collaborative people in a particular group, and any flaws in the dissemination of information on the same. It should be noted also, that this research presents a way to define participation and affinity of people in a given context. The results show that it is possible to correlate the data of users on Twitter, with their indices regarding the application of the metrics data with social network analysis and credit companies in order to quantitatively analyze the relationship of these users on various aspects rated the credit crunch.